Total Placenta Previa with High-risk MAP and Transverse Lie Fetal Position - Raden Theodorus Soepraptomo; Fitri Hapsari; Teddy Wijaya (HM Publisher, 2020)
Placenta accreta is one of the emergency conditions and has resulted in increased mortality and morbidity of pregnant women due to the massive obstetric hemorrhage. Placenta accreta can lead to secondary complications including coagulopathy, multisystem organ failure, acute respiratory distress syndrome, need for repeat surgery, and death. Assessment by anesthesia should be carried out as early as possible before surgery to reduce or even eliminate morbidity and mortality. In this report, we present the case of a patient with total placenta previa and high-risk MAP score with a transverse lie fetal position. The various anesthetic treatments and transfusion strategies are discussed with a multidisciplinary approach to delivery.